Keeping enzymes kosher. (4th May 2015) - Fischer, Johan
<x xml:space="preserve">Abstract</x> Biotech companies increasingly seek certification for compliance with religious and dietary requirements in order to address new consumer markets. Technology plays a crucial role in such inspections alongside centuries old traditions and practices.